Insect molecular biology and biochemistry - Gilbert, Lawrence I. (Elsevier/Academic Press, 2012)
'Insect Molecular Biology and Biochemistry' is designed for those who desire a comprehensive yet concise work on important aspects of this topic. This volume contains ten fully revised or rewritten chapters from the original series as well as five completely new chapters on topics--